Indoor air quality in enclosed cafeteria at UiTM, Shah Alam / Maizatul Akma Said - Said, Maizatul Akma (Faculty of Architecture, Planning and Surveying, 2013)
Indoor air pollution is consistently reported to be two to five times and occasionally up to 1,000 times higher than outdoor levels. This is alarming considering than the majority of people tent to spend an average of 70% to 96% of their indoor environments. In enclosed cafeteria it has the same situation but not almost users use it and spend an average time in that area. Indoor Air Quality (IAQ), however, is still a relatively unexplored topic in Malaysia. In this study was therefore conducted to examine IAQ from a local perspective. IAQ monitoring was conducted in a selected sample of IAQ in enclosed cafeteria area an impact on human comfort. The three of enclosed cafeteria area were monitored. IAQ parameters measured in this study include temperature; relative humidity and air velocity also have carbon dioxide and carbon monoxide. IAQ measurements were taken in one of the case study were divide into three type of area in that area that is dining area, cooking area and toilet (if have). The overall results shows the IAQ in enclosed cafeteria at UiTM, Shah Alam were not less than the limit of parameters existing IAQ guidelines and standards. However, it still need a good ventilation and air conditioning systems.